1990
DOI: 10.1177/153944929001000301
|View full text |Cite
|
Sign up to set email alerts
|

Values, Salience, and Job Satisfaction: Male and Female Occupational Therapists' Responses

Abstract: A matchedpeer study of55 male and 55 female respondentsfrom a national survey ofoccupational therapists in Canada (N = 1,400) was completed in order to examine the level of value endorsement and job satisfaction. Respondents were matched according to position, educational level, years sincegraduation, marital status, and area of residence. Data from the Life Roles Inventory (LRI) was analyzed using discriminant analysis; results showed that males endorsed Risk and Mvancement more strongly than their female coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…A number of subsequent studies of occupational therapists examined different aspects of job satisfaction . These included male and female differences (Taylor, Madill & Macnab, 1990), career patterns (Madill et al, 1986a), work-related reinforcer patterns (Madill, Vargo & Brintnell, 1990), and issues of working and family roles of occupational therapists (Madill et al, 1986b). These studies demonstrated that female occupational therapists consistently valued the intrinsic elements of their work highly, with their home/family role rated as most important (Madill, Vargo & Brintnell, 1990).…”
Section: The Work Importance Study and Related Research About Occupatmentioning
confidence: 89%
See 1 more Smart Citation
“…A number of subsequent studies of occupational therapists examined different aspects of job satisfaction . These included male and female differences (Taylor, Madill & Macnab, 1990), career patterns (Madill et al, 1986a), work-related reinforcer patterns (Madill, Vargo & Brintnell, 1990), and issues of working and family roles of occupational therapists (Madill et al, 1986b). These studies demonstrated that female occupational therapists consistently valued the intrinsic elements of their work highly, with their home/family role rated as most important (Madill, Vargo & Brintnell, 1990).…”
Section: The Work Importance Study and Related Research About Occupatmentioning
confidence: 89%
“…These studies demonstrated that female occupational therapists consistently valued the intrinsic elements of their work highly, with their home/family role rated as most important (Madill, Vargo & Brintnell, 1990). Male occupational therapists endorsed risk and advancement more highly and rated study as more important than their female colleagues (Taylor et al, 1990).…”
Section: The Work Importance Study and Related Research About Occupatmentioning
confidence: 94%
“…À l'intérieur de la dyade conjugale, les femmes sont également plus insatisfaites de leur vie de couple que leurs conjoints (Schumm, Bollman, & Jurich, 1997;Schumm, Resnick, Bollman, & Jurich, 1998;Schumm & Silliman, 1996;Schumm, Webb, & Bollman, 1998). Toutefois, en opposition aux recherches précédentes, d'autres études effectuées auprès de professionnels ne repèrent pas de différence dans le niveau d'ajustement dyadique (Burley, 1995;Taylor, Madill, & Macnab, 1990). …”
Section: Engagement Dans Les Rôlesunclassified
“…Ce résultat est conforme à ce qui avait été observé dans la recension des écrits, puisque aucune différence n'avait pu être relevée entre les conjoints et leurs niveaux d'engagement marital (p. ex., Burley, 1995;Taylor et al, 1990). La longue durée de la relation maritale des couples de l'échantillon à l'étude, qui vivent en couple depuis en moyenne 17 années, pourrait expliquer que les conjoints ne s'engagent pas différemment dans le rôle de conjoint.…”
Section: Interprétation Des Données Sociodémographiquesunclassified
“…In the United States, the percentage of male occupational therapists did increase from 5% (Rider & Brashear, 1988) to 5.7% (American Occupational Therapists Association (AOTA) 1990 member data survey, personal communication, March 15, 1994). These percentages have remained relatively constant although attempts have been made to recruit more males (Madill, 1987;Readman, 1992;Taylor, Madill, & Macnab, 1990;Tysinger & Whiteside, 1987;Wyrick & Stern, 1987). Men who do become occupational therapists tend to stay in the profession for short periods of time (Brown, 1991;Madill 1987;Posthuma, 1983), and may perceive the profession as a stepping stone to medicine or other health fields Uantzen 1973; Taylor et al, 1990).…”
mentioning
confidence: 96%